Excitons and interband terahertz transitions in narrow-gap carbon nanotubes - Portnoi, M. E. (Animo Repository, 2013)
We show, via a solution of the quasi-one-dimensional two-body problem applied to a Dirac system, that excitonic effects suppress the one-dimensional Van Hove singularity in single-walled carbon nanotubes with narrow band gaps. © 2013 IEEE.